Love, Hate And The Emergence Of Self In Addiction Recovery (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
The authors argue that the formation of self is at the heart of many addiction issues. Likewise issues of love (sought) and hate (found) are central to both the formation of a self vulnerable to addiction and to fostering recovery. So the negative feelings towards addicts (hate) is not simple prejudice, but inherent to the condition itself. As such this needs careful reflection by therapists. The authors argue that love, as compassion, is the central healing feature in addiction recovery.
Keywords: Addiction; love; hate; self; identity; recovery